Integration of Fintech and Digital Marketing in Optimizing Accounting Operations and Management Accounting - Al-Ababneh, Hassan Ali; Amoush, Arwa H.; Alshawawreh, Ali Ra’ed; Tawdrous, Maher Ibrahim; Khader, Jameel Ahmad (International Review of Management and Marketing, 2026)
This study aims at assessing how accounting processes and management accounting can be optimized using fintech products and digital marketing. The topicality of the matter is predetermined by the intensive growth of the fintech platform, the growing significance of the channel of digital interaction with the customer, the growth of the needs in the quality of corporate data. This paper implements the stochastic frontier analysis (SFA) to estimate the efficiency and suggested approach decomposes the actual efficiency of accounting operations, without considering the random error, into the input of fintech tools, digital marketing, data quality, and the degree of automation. The sample of the research will consist of six companies of different countries and industries, and the data obtained in 2022 -2024 is set to be used to measure the dynamics of efficiency and digital transformation. The results suggest that fintech solutions alleviate the accounting processes inefficiencies, and the digital marketing indirectly affects the management accounting due to the data quality improvement and structure. A cumulative impact of these factors will generate a sustainable, holistic benefit, increasing accuracy, speed, and compliance of financial processes. The novelty of the research is the use of SFA to assess the digital integration in accounting that allows measuring the synergies between fintech and digital marketing and determining the levels of digital maturity.